Ensaiando com Almada Negreiros, um diálogo entre a ciência e a literatura no início do século XX - Barreira, Carla de Fátima Martins (2009)
The literature encompasses people culture, the society historical context and reflects human feelings of a certain time, in prose and verse. Thus, it reflects humanity history with all its social, emotional and scientific caracteristics. A dialogue between science and literature becomes natural, since they both drink from the same source: the man. We studied Almada Negreiros works, accenting their tests, considering the Orfeu Generation and the Vanguard Movements, which innovated the arts. We considered a possible conjunction with Émile Zola naturalism. This accent makes possible a science history with an interface between literature and science in the second half of the nineteenth century and early twentieth